Effect of Leadership Style of the Head of the Community Health Center and Other Determinants on the Health Personnel Performance in Boyolali, Central Java - David Marwandi; Endang Sutisna Sulaeman; Pawito Pawito (Journal of Health Policy and Management, 2020)
Background: Leadership in health services is needed to utilize resources efficiently, design management processes, and encourage health workers to work towards achieving common goals. The purpose of this study was to analyze the effect of leadership style of the head of community health center and other determinants on the performance of health personnel.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted in Boyolali, Central Java, from June to July 2019. A sample of 206 health personnel from 22 community health centers was selected for this study. The dependent variable was the performance of health personnel. The independent variables were perceived transformational leadership, perceived income, type of community health center, accreditation status, education level, tenure, training, community health center, and employee status. The data were collected by questionnaire and analyzed by a multilevel multiple linear regression run on Stata 13.Results: Health personnel performance increased with transformational leadership style (b= 2.23; 95% CI= 0.94 to 3.52; p <0.001), type of health workers (b= 1.80; 95% CI= 0.10 to 3.49; p = 0.037), and accreditation status (b= 3.01; 95% CI= 0.58 to 5.44; p= 0.015). Health personnel performance increased with education ≥Diploma III (b= 0.55; 95% CI= -1.46 to 2.56; p= 0.592), tenure ≥3 years (b= 0.05; 95% CI= -1.49 to 1.59; p = 0.947), adequate income (b= 1.16; 95% CI= -0.10 to 2.42; p= 0.072), and had attended training (b= 0.67; 95% CI= -0.68 to 2.03; p= 0.329), but they were statistically non-significant. Health personnel performance decreased with the status of civil servant (b= -1.32; 95% CI= -3.82 to 1.16; p= 0.298) and treatment status of community health center with hospitalization (b= -2.97; 95% CI = -5.03 to -0.91; p = 0.005).Conclusion: Health personnel performance increases with transformational leadership style, type of health workers, accreditation status, education ≥Diploma III, tenure ≥3 years, adequate income, and had attended training. Health personnel performance decreases with the status of civil servant and treatment status of community health center with hospitalization.Keywords: transformational leadership style, health personnel, performance.Correspondence:David Marwandi. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: david.marwandi88@gmail.com. Mobile: +6281348789393Journal of Health Policy and Management (2020), 5(1): 74-84https://doi.org/10.26911/thejhpm.2020.05.01.07